Optimization of TiO2/ZSM-5 photocatalysts: Energy band engineering by solid state diffusion method with calcination. Issue 4 (August 2021) - Duan, Xu; Yang, Jian; Hu, Guang; Yang, Chen; Chen, Yangfan; Liu, Qingcai; Ren, Shan; Li, Jiangling
Abstract: In this work, based on a type of energy band engineering strategy as calcination, TiO2 /ZSM-5 hybrids for photodegradation of methyl orange (MO) in water under UV light have been developed via a facile solid state diffusion method. Effects of varied calcination temperatures on TiO2 /ZSM-5 hybrids have been systematically characterized including XRD, FT-IR, SEM, TEM, EDX mapping, BET, PL, EIS, UV–vis DRS, active species trapping experiments and Mott-Schottky curves. It was found that the calcination temperature influenced photocatalytic activity, typically on physicochemical properties of materials and adjustment for the energy gap and band position of TiO2 . The XRD analysis revealed that hybridization of ZSM-5 kept the crystal phase of TiO2 as anatase unchanged with the high-rising calcined temperature. The optimum sample calcined at 450 °C named as Z-T (450) presented nearly 99% degradation rate for MO, owing to optimal uniform distribution, highest specific surface area and best charge separation/transfer efficiency. The FT-IR comparison result that the functional groups and peak strength of the used catalyst were alike as before, showed the stability of photocatalyst. Adoption of calcination strategy does provide not only a clean, low-cost and highly efficient path to approach the complete degradation of azo dyes, but also a chance for photocatalytic technology to fulfill the implementation in industrial applications. Graphical Abstract: ga1 Highlights: SSD method with calcination achieved energy band engineering of TiO2 /ZSM-5 hybrids. The optimal TiO2 /ZSM-5 hybrid degraded nearly 100% of methyl orange. The synergy between TiO2 and ZSM-5 of different calcined temperature was contrastively studied. The photocatalytic mechanism of TiO2 /ZSM-5 hybrids was proposed from the perspective of energy band theory.